Information Sources and Key Preferred People of Iranian University Students about Organ Donation. (August 2017) - Ghaffari, Mohtasham; Rakhshanderou, Sakineh; Latifi, Marzieh; Najafizadeh, Katayoun; Ramezankhani, Ali; Soleimaninejad, Marzieh
Abstract : Introduction: The aim of this study was determining information resources and key preferred people among Shahid Beheshti University of Medical Sciences about organ donation. Method and materials: This was a cross- sectional study being performed among Shahid Beheshti University of Medical Science's students during Dec 2016-Feb2017. 438 students of three school in SBMU were selected using multi stage sampling method. Participants completed a questionnaire, that is validity and reliability were performed previously. Questionnaires were completed without name and were collected by investigators. Data were analyzed by SPSS version 16. Results: 59.3% (n =259) of students were male and 40.7% (n =178) were female. The respondents had a mean age of 22.47 ± 5.79 years. Television was found to the main in this aspect to obtain information and then Internet was second one, but families were lowest. 11.9% of students 'family have an organ donation card. 45 respondents (10.3%) thought that organ donation causes spread disease. Students respectively announced their families 65.8%, friends 30.6%, doctors 29.5%, religious leaders 22.8% and teachers18.5% as the most influential people on their decision for getting organ donation card. Conclusion: According results, it was recommended appropriate interventions such as health education and advocacy, especially through national Television. Also we could say that focusing on families could lead more effective interventions about topic such as organ donation and getting organ donation card. References: 1. Feeley T.H, Tamburlin J, Donald E, Vincent MA. An Educational Intervention on Organ and Tissue Donation for First-Year Medical Students. Progress in Transplantation. 2008; 18(2): 103-108 2. Heuer M, Radunz S, von Hugo F, Kirchner C, Wittenburg N, Stammen K-H, et al. Online intervention study-willingness to donate organs among the employees of a German University. European Journal of Medical Research. 2014;19(1):43. 3. Piccoli GB, Soragna G, Putaggio S, Burdese M, Longo P, Rinaldi D, et al. Efficacy of an educational program on dialysis, renal transplantation, and organ donation on the opinions of high school students: a randomized controlled trial. Transplant Proc. 2004 Apr;36(3):431–2.